2015
DOI: 10.32637/orli.v45i2.119
|View full text |Cite
|
Sign up to set email alerts
|

Modified transnasal endoscopic medial maxillectomy with inferior turbinate flap for dentigerous cyst

Abstract: Background: Dentigerous cyst is one of the most frequent types of odontogenic cyst that usually involving an impacted, supernumerary or ectopically erupted tooth. One of the non-dental sites for ectopiceruption is the maxillary sinus. The traditional approach under such circumstances is a Caldwell-Luc maxillotomy, but this type of procedure may result in significant long-term complications. Endoscopic transnasal medial maxillectomy (ETMM) has several advantages, such as good il lumination, as wellas clear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Caldwell-Luc operation is still one of the leading types of surgery in case of giant follicular cysts of the sinus. The endoscopicassisted removal of the cyst and associated tooth has not only a variety of modifications 27,36,37 but also its performance has some limitations. Case of Emanuelli et al 27 showed that it can be problematic, during the endoscopic surgery, to remove lateral sclerotic wall of the cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Caldwell-Luc operation is still one of the leading types of surgery in case of giant follicular cysts of the sinus. The endoscopicassisted removal of the cyst and associated tooth has not only a variety of modifications 27,36,37 but also its performance has some limitations. Case of Emanuelli et al 27 showed that it can be problematic, during the endoscopic surgery, to remove lateral sclerotic wall of the cyst.…”
Section: Discussionmentioning
confidence: 99%